2021
DOI: 10.1021/acs.energyfuels.1c00351
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Hydrothermal Synthesis of Nickel Cobalt Telluride Nanorods for Hybrid Energy Storage Systems

Abstract: Herein, we delineate the one-pot preparation of nickel cobalt telluride nanorods (NiCoTe NRs) by the hydrothermal method using cetyltrimethylammonium bromide and ascorbic acid as reducing agents. The Ni0.7Co0.3Te NRs (NCT-1 NRs) were investigated with different characterization techniques, such as X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. Magnetic measurement shows the paramagnetic behavior of the prepared samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 64 publications
(118 reference statements)
1
16
0
Order By: Relevance
“…Structural and morphological studies, such as XRD, XPS, BET, and TEM, for the prepared samples have been analyzed and discussed in our previous report. 17 Figure S1(a,b) displays the FESEM images of NCT 1 and NCT W. The prepared materials show uniform morphology of nanorods. Figure S1c reveals the the XRD pattern for NCT-W corresponds to nickel telluride [International Centre for Diffraction Data (ICDD) number 00-065-3665] and cobalt telluride (ICDD number 00-089-7180).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural and morphological studies, such as XRD, XPS, BET, and TEM, for the prepared samples have been analyzed and discussed in our previous report. 17 Figure S1(a,b) displays the FESEM images of NCT 1 and NCT W. The prepared materials show uniform morphology of nanorods. Figure S1c reveals the the XRD pattern for NCT-W corresponds to nickel telluride [International Centre for Diffraction Data (ICDD) number 00-065-3665] and cobalt telluride (ICDD number 00-089-7180).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Structural and morphological studies, such as XRD, XPS, BET, and TEM, for the prepared samples have been analyzed and discussed in our previous report. 17 where α o, I, I s , and β ef f are the linear absorption coefficient at 532 nm, input laser intensity, saturation intensity, and two photon absorption coefficient, respectively. The corresponding propagation equation is given as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In addition, compared with S and Se, Te possesses lower electronegativity, which makes metal tellurides have stronger metal character, endowing them with ferromagnetism behavior and properties. 12,13 When employed as electrocatalysts, metal tellurides outperform other chalcogenide-based catalysts. Wang et al 14 reported that a NiTe nanosheet film on nickel foam (NiTe/NF) exhibits remarkable oxygen evolution reaction activity requiring an overpotential as low as 262 mV to deliver an anodic current density of 10 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the energy storage theory, pseudocapacitors with fast reversible Faradic reactions on the electrode surface can effectively enhance the specific capacitance of electrode materials . Therefore, some pseudocapacitive materials have been designed, such as metallic and nonmetallic heteroatoms (nickel, silver, copper, iron, nitrogen, boron, phosphorus, etc. ).…”
Section: Introductionmentioning
confidence: 99%